FRI0006 Protein citrullinations by pad enzymes promote dendritic cell transdifferentiation into osteoclast and generate targets for ra-specific antibodies. (15th June 2017) - Réthi, B; Krishnamurthy, A; Ytterberg, J; Sun, M; Joshua, V; Wähämaa, H; Tarasova, N; Steen, J; Malmström, V; Catrina, AI
Abstract : Background: Immature dendritic cells (DCs) are able to trans-differentiate into osteoclasts (OCs) although the mechanisms regulating this process are little understood. We have recently described an important role for protein citrulliantion and peptidylarginine deiminase (PAD) enzyme activity in the regulation of OC development (1). Objectives: We studied the molecular bases of DC-OC trans-differentiation and aimed at understanding the role of protein citrullination in this process. Methods: Monocyte-derived DCs and peripheral blood CD1c+ DCs were cultured in the presence of osteoclastogenic cytokines. Polyclonal ACPAs were isolated from the serum of RA patients and applied in OC cultures. DC and OC differentiation was analyzed in vitro using gene expression analyses, flow cytometry-based methods, DC-T cell co-culture experiments, tartrate-resistant acid phosphatase stainings and osteolysis assays. Protein citrullination was monitored with the help of mass spectrometry. PAD activity was measured by ELISA. Results: Different DC types showed different capacities to develop into OCs. OC-prone DCs were characterized by little immunogenicity and their development was potentiated by the increase of lactic acid, a side product of glycolytic metabolism. The more immunogenic DC types, characterized by prominent ability to migrate towards secondary lymphoid tissues and trigger T cell activation, showed a limited capacity to develop into OCs (2). The differentiation switch towards the OC lineage was associated with increased activity of the Protein Arginine Deiminase (PAD) enzymes and with higher level of protein citrullination in DCs. The PAD inhibitor Cl-Amidine efficiently interfered with OC development form DC precursors. In addition, the deposition of citrullinated proteins on the cell surface made the cells sensitive for anti-citrullinated protein autoantibodies, which could further stimulate DC-OC trans-differentiation through inducing the cytokine IL-8. Conclusions: Our results indicated that DCs are heterogenic in their ability to form OCs and lineages for immunostimulatory and OC-prone DCs might separate early during DC differentiation. Plasticity towards OC differentiation might be influenced by the metabolic environment and the upregulation of PAD activity in DCs. References: Krishnamurthy A et al. Ann Rheum Dis 2016. Nasi A et al. J Immunol 2013. Disclosure of Interest: None declared